Writ on water : the sources and reach of film imagination - Warren, Charles, 1948-2021 (State University of New York Press, 2022)
"A powerful and original statement on the nature of film and the intimate relation of "film imagination" to our lives as human beings in the world"-- Provided by publisher.
Keywords: Motion pictures -- Philosophy.; Motion pictures -- History.; Film criticism.; Cinéma -- Histoire.; Critique cinématographique.; Cinéma -- Philosophie.; Film criticism; Motion pictures; Motion pictures -- Philosophy; History